If . represents one of the operations +, -, and x, is k. (l+m)=(k.l) + (k.m) for all numbers k, l, and m?
(1) k.1 is not equal to 1.k for some numbers k.
(2) . represents subtraction
I am not sure how to work through this?
esledge Wrote:First, you should try to rephrase the question. You know there are 3 possibilities for the operator: addition, subtraction, multiplication.
If the operator is addition, the question really is:
Is k + (l + m) = (k + l) + (k + m) for all numbers k, l, and m?
Is k + l + m = 2k + l + m for all numbers k, l, and m?
Is k = 2k for all values of k?
We can see that the answer is NO when the operator is addition.
If the operator is subtraction, the question really is:
Is k - (l + m) = (k - l) + (k - m) for all numbers k, l, and m?
Is k - l - m = 2k - l - m for all numbers k, l, and m?
Is k = 2k for all values of k?
We can see that the answer is NO when the operator is subtraction.
If the operator is multiplication, the question really is:
Is k * (l + m) = (k * l) + (k * m) for all numbers k, l, and m?
Is kl + km = kl + km for all numbers k, l, and m?
We can see that the answer is YES when the operator is multiplication.
So, if the answer must be NO when the operator is addition or subtraction, but the answer must be YES when the operator is multiplication, the ultimate question here is: "Is the operator multiplication, or one of the other two choices?"
Statement (1) SUFFICIENT:
Try out the three operators to see which one matches what the statement tells us.
Addition: (k + 1) = (1 + k) for all values. Therefore, the operator is not addition.
Subtraction: (k - 1) = (1 - k) when k = 1, but not for other values of k. Therefore, the operator could be subtraction.
Multiplication: (k * 1) = (1 * k) for all values. Therefore, the operator is not multiplication.
Thus, statement (1) tells us the operator is subtraction, sufficiently answering the rephrased question.
Statement (2) SUFFICIENT:
This is the easier statement, as it answers the rephrased question outright.
{By the way, there is an error in the OG explanation. In the discussion of statement (1), it says "k + 1 = 1 + k, and also k - 1 = 1 - k." They meant "...and also k * 1 = 1 * k."}
If "." is "-" then k. (l+m)=(k.l) + (k.m) reduces to k = 2k which can be true if k=0 and nothing else. Hence st1 could be yes or no depending on k.
St2 tells us the same thing. Hence I guess the ans is E. If not please explain.